ZKSCAN3 promotes ovarian cancer cell proliferation by increasing HSPB1 expression - Ke, Qian; Li, Zhenyong; Fan, Li; Li, Neng; Sun, Lidong; Zhao, Hongbo; Song, Tanjing (Frontiers in Molecular Biosciences, 2025)
Ovarian cancer has the worst prognosis among major gynecological cancers. Current therapies include platinum, Taxol, angiogenesis inhibitors, and poly[ADP-ribose]polymerase (PARP) inhibitors. However, resistance develops in most ovarian cancer patients. Identification of more pro-tumor factors in ovarian cancer may provide insights into ovarian cancer biology and therapy. In this study, we find ZKSCAN3, a zinc-finger transcription factor, is overexpressed in ovarian cancer. We show that ZKSCAN3 promotes ovarian cancer cell proliferation. Through RNA-Seq and chromatin immunoprecipitation (ChIP)-seq, HSPB1 is identified as a target gene of ZKSCAN3. HSPB1 expression is significantly decreased upon suppressing ZKSCAN3 expression. Suppressing HSPB1 expression also inhibits ovarian cancer cell proliferation. In contrast, expressing exogenous HSPB1 partially rescues the cell proliferation in ZKSCAN3 knockdown cells, which supports HSPB1 as a functional target gene of ZKSCAN3. Collectively, our study uncovers a functional ZKSCAN3-HSPB1 axis that promotes ovarian cancer cell proliferation.